Identification of prognostic genes associated with tolerogenic dendritic cells in gastric cancer based on transcriptomic data - Shenyu Luo; Guozhi Yang; Yuhua Yuan; Yong Zhang; Yihua Kang; Zhengrong Wen; Wei Liu; Ying Liu (PLoS ONE, 2026)
Background Tolerogenic dendritic cells have a pivotal function in treating autoimmune illnesses, atopic diseases, and neoplasms. The precise mechanism by which Tolerogenic dendritic cells function in gastric cancer remains incompletely understood. Therefore, this research explored potential genes with prognostic value related to Tolerogenic dendritic cells in gastric cancer, to identify novel therapeutic targets that could provide valuable insights for the clinical treatment of gastric cancer. Results Five prognostic genes (CXCL1, INHBA, ASCL2, RNASE1, and GPX3) were finally obtained to construct the risk model. Immune infiltration analysis revealed that GPX3 exhibited significant positive associations with various immune cell populations, particularly regulatory T cells. While ASCL2 was weakly associated with almost all immune cells. These results suggested that there was a complex correlation between prognostic genes and immune cells. The analysis of drug sensitivity demonstrated higher IC50 values for compounds such as BIBW2992 in high-risk group relative to low-risk group. A reverse pattern was observed for GSK269962A and similar drugs, which showed significantly higher IC50 values in low-risk group than high-risk group. Conclusion The present study revealed five prognostic genes and constructed a predictive model, which provided a theoretical basis for the correlation linking Tolerogenic dendritic cells to gastric cancer, and established potential therapeutic strategies in managing gastric cancer. Single-cell analysis revealed that INHBA, ASCL2, and CD36 exhibited marked differential expression in dendritic cells.